Development of an AI-Assisted Teacher Training Module for Creating Digital Storybooks in Elementary Schools - Kartika Pradiningtyas; Bambang Ismanto; Stefanus C. Relmasira (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Artificial intelligence offers new opportunities for elementary school teachers to design creative literacy-based learning media, yet its pedagogical use requires structured guidance, ethical awareness, and practical training. This study aimed to develop and evaluate an AI-assisted teacher training module for creating digital storybooks in elementary schools. The study used a research and development design with a mixed-method approach based on the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation. The participants were 18 teachers at SD Negeri Getasan, Indonesia. Data were collected through interviews, expert validation sheets, teacher response questionnaires, cognitive tests, product assessment rubrics, reflection questionnaires, observation, and documentation. Quantitative data were analyzed using descriptive statistics, while qualitative data were used to interpret teacher needs, implementation experiences, and product refinement. The results showed that teachers had strong readiness to adopt AI, although they still needed support in story writing instruction and structured digital storybook production. Expert validation confirmed that the module was highly feasible, with scores of 88.75% from the material expert, 90.63% from the media expert, and 87.50% from the educational practitioner. The practicality test obtained 90.55%, while cognitive effectiveness reached 79.50%. Teachers’ digital storybook products achieved an average score of 3.63 and were categorized as very good. Reflection and usefulness results also indicated positive acceptance and strong potential for sustainable implementation. The main contribution of this study is not limited to producing a training module, but lies in offering an integrated teacher professional development framework that connects AI literacy, digital storytelling pedagogy, ethical evaluation, creative authorship, and school portfolio documentation.